Design and analysis of a K‐band wideband voltage‐controlled oscillator with robust start‐up and frequency boost. Issue 14 (1st November 2015) - Sun, Junyi; Boon, Chirn Chye; Yi, Xiang; Lim, Wei Meng; Meng, Fanyi
Abstract : This study presents a K‐band differential voltage‐controlled oscillator (VCO) with robust start‐up. A hybrid technique that combines open‐loop digitally controlled tail current with switchable auxiliary cross‐coupled pairs (ACCPs) is proposed to ensure robust start‐up for wideband operation. Compared with prior closed‐loop current controlling method, the proposed technique does not suffer from phase‐noise degradation. Furthermore, by evenly distributing the ACCPs, transistors with smaller size are allowed to achieve the same start‐up condition, which leads to frequency boost and phase‐noise improvement. Implemented in 0.18 μm complementary metal–oxide–semiconductor technology, the VCO achieves a wide‐frequency tuning range of 21.4–26.29 GHz (20.5%) and a low phase noise of −108.8 dBc/Hz at 1 MHz offset from 25.8 GHz carrier frequency. At 1.1 V power supply, the power consumption of the core circuit is 7.9–11.4 mW across the entire output frequency range.